Some implications of recidivism as a criterion in program evaluation - Homant, Robert J. (American journal of criminal justice, 1983)
This article discusses the use of recidivism statistics in corrections. Recent attacks on the relevance of recidivism have come from both the left and the right of the political spectrum. It is argued here that despite these attacks there are still reasonable grounds for maintaining rehabilitation as a major goal, and recidivism as a meaningful criterion of that goal. The purpose of this essay, however, is not so much to defend the use of recidivism, as to caution against its narrow use. Examples are given from the areas of parole contracts, juvenile awareness programs and approaches to probation and parole to illustrate the possible misuse of recidivism. It is argued here that it is more important to evaluate the effect of a program on a system, than to try to evaluate its impact on individual offenders.